Development of heterodox economics at public German universities since the 1970s - Sebastian Thieme; Arne Heise (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2016)
This article discusses the development of 'heterodox' economics at universities in Germany since the 1970s. Based on Lakatos' concept of scientific research programmes (SRP), the article introduces a classification of economics in order to clarify the understanding of variety within economics, especially in the case of Germany. Based on this classification and taking into account the different kinds of capital (economic, social and symbolic) available to heterodox economists, this article aims to show how heterodox economics in Germany has developed from the early 1970s until the present day. It will be shown that the heterodox schools expanded in the 1970s, but marginalisation took hold again by the 1980s and ultimately left German heterodox economics in a state of near-extinction today. From this, it follows that the history of heterodoxy in Germany is an unequal 'battle of the paradigms', and can only be told as the story of a failure.
Keywords: A11; B20; B50; Z; 330; heterodox economics; pluralisation; philosophy of science; sociology of science; Germany